P951Autonomic nervous function and excitability of the accessory pathway in pediatric patients with Wolff-Parkinson-White ECG. (18th June 2020) - Galli, A; Lippolis, M; Barbolini, E; Belmonte, M; Ambrosini, F; Gherbesi, E; Chierchia, G B; De Asmundis, C; Lombardi, F
Abstract: Abrupt loss of preexcitation identifies low-risk Wolff-Parkinson-White (WPW). We hypothesize that the autonomous nervous system (ANS) modulates the conduction of the accessory pathway (AP). PURPOSE To compare heart rate variability (HRV) in children with (WPWi) and without (WPWp) intermittent preexcitation.  METHODS The study conforms to the Declaration of Helsinki.  18 WPW children and controls performed ECG Holter for HRV analysis. Intermittent preexcitation was defined as abrupt loss of WPW pattern. Kolmogorov-Smirnov test confirmed normal distribution of data. T-test and Fisher"s exact test were used for continuous and categorical variables. Multivariate regression excluded the effect of potential confounders (figure 1 shows correlation between HRV and HR).  RESULTS WPWi (11/18, 61.1%) have higher HRV as compared with WPWp. Despite WPWp patients are younger, with higher HR, corrected multivariate analysis confirmed significant differences (table 1), also between WPW patients and controls.  CONCLUSIONS WPW patients have lower HRV. WPWp may have worst autonomic control to the excitability of AP.